PENGARUH MODEL PEMBELAJARAN MURDER TERHADAP HASIL BELAJAR KOGNITIF DAN KETERAMPILAN SOSIAL - Marzuki, Ismail (Bioscientist : Jurnal Ilmiah Biologi, 2015)
The research used quasi experimental with pretest-postest control group design. The research used population study that was VIII A and VIII B class as experimental and control group with the average number of the student at each class 22 and 20 students. The total number of the population 42 students. The data gathering used test and questioner and the then the data analysis used ttest formulation. Based on statistical analysis was gotten t-test score was higher than t-table (5,590 > 2,021). Therefore, it took conclusion that there was significant effect of number learning model toward students’ cognitive achievement and social skill at VIII class of SMPK ST. Antonius Ampnenan.